School-Based Management During the Covid-19 Pandemic: A Study at The Integrated Islamic Vocational School - Sari, Sesmita Maya; Setyaningsih, Rini (Journal of Islamic Education Students (JIES), 2023)
The Covid-19 pandemic has brought significant challenges to various aspects of society, including the management of education. In light of this, this study aims to examine the implementation and effectiveness of School-Based Management (SBM) during the Covid-19 pandemic at an Integrated Islamic Vocational School. The research adopts a qualitative descriptive approach, employing field research methods such as interviews, observations, and documentation. The informants for this study were selected using Purposive Sampling, including key informants and supporting informants. The study's findings reveal that the Integrated Islamic Vocational School has successfully implemented school policies while prioritizing efficiency and effectiveness during the Covid-19 pandemic. The school has fostered effective teamwork to address challenges and navigate government policies, ensuring the continuity of the educational process and its acceptance by students. The implementation of SBM during this challenging period has demonstrated its efficacy in managing the school and optimizing available resources.┬á